Cotton Ascorbate Oxidase Promotes Cell Growth in Cultured Tobacco Bright Yellow-2 Cells through Generation of Apoplast Oxidation - Li, Rong (Int J Mol Sci, 2017)
Ascorbate oxidase (AO) plays an important role in cell growth through the modulation of reduction/oxidation (redox) control of the apoplast. Here, a cotton (Gossypium hirsutum) apoplastic ascorbate oxidase gene (GhAO1) was obtained from fast elongating fiber tissues. GhAO1 belongs to the multicopper oxidase (MCO) family and includes a signal peptide and several transmembrane regions. Analyses of quantitative real-time polymerase chain reaction (QRT-PCR) and enzyme activity showed that GhAO1 was expressed abundantly in 15-day post-anthesis (dpa) wild-type (WT) fibers in comparison with fuzzless-lintless (fl) mutant ovules. Subcellular distribution analysis in onion cells demonstrated that GhAO1 is localized in the cell wall. In transgenic tobacco bright yellow-2 (BY-2) cells with ectopic overexpression of GhAO1, the enhancement of cell growth with 1.52-fold increase in length versus controls was indicated, as well as the enrichment of both total ascorbate in whole-cells and dehydroascorbate acid (DHA) in apoplasts. In addition, promoted activities of AO and monodehydroascorbate reductase (MDAR) in apoplasts and dehydroascorbate reductase (DHAR) in whole-cells were displayed in transgenic tobacco BY-2 cells. Accumulation of H(2)O(2), and influenced expressions of Ca(2+) channel genes with the activation of NtMPK9 and NtCPK5 and the suppression of NtTPC1B were also demonstrated in transgenic tobacco BY-2 cells. Finally, significant induced expression of the tobacco NtAO gene in WT BY-2 cells under indole-3-acetic acid (IAA) treatment appeared; however, the sensitivity of the NtAO gene expression to IAA disappeared in transgenic BY-2 cells, revealing that the regulated expression of the AO gene is under the control of IAA. Taken together, these results provide evidence that GhAO1 plays an important role in fiber cell elongation and may promote cell growth by generating the oxidation of apoplasts, via the auxin-mediated signaling pathway.